Endophytic fungi associated with the restinga bromeliads the National Park of Jurubatiba Restinga, Rio de Janeiro - Brazil (Research, Society and Development, 2020)
Throughout evolution, plants have adapted to different terrestrial habitats and developed the ability to interact with different species of living things, among which, fungi stand out, and have shown great biotechnological or scientific interest and have been isolated and studied from plants in different natural biomes. Thus, the objective was to identify cultivable endophytic fungi associated with Bromeliaceae from the Jurubatiba restinga, state of Rio de Janeiro. Two collections were made in the Restingas de Jurubatiba National Park (PNRJ), located on the north coast of the state of Rio de Janeiro. Samples of healthy plant leaves for the isolation of endophytic fungi were collected from the species of bromeliads inhabiting this restinga: Aechmea nudicaulis (L.) Griseb. (collection 1) and Bromelia antiacantha Bertol (collection 2). Plants were collected at random in order to cover their most representative range. In the laboratory, under conditions aseptic procedures, an isolation procedure for endophytic fungi kept under storage was carried out and, later, identification of isolated fungi, under an optical microscope. The fungal genera were identified: Aspergillus sp., Bipolaris sp., Curvularia sp., Monilia sp., Nigrospora sp., Penicillium sp., Pestalotiopsis sp., And Trichoderma sp. Isolates of Bipolaris sp., Curvularia sp. and Monilia sp. were identified in both collected bromeliads. Within each genus, the isolates were grouped and characterized into subtypes and, based on a bibliographic survey, the endophytic fungi found could be studied for different biotechnological purposes and applicability in different aspects of knowledge, and this was the first report of endophytic fungi. in these species of bromeliads.